1989
DOI: 10.1677/joe.0.1200393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin, glucose and ACTH on corticosterone production by fetal adrenal cells from diabetic rats

Abstract: Experiments were carried out on Sprague-Dawley rats to determine whether changes in fetal corticosterone levels during maternal diabetes were caused by the accompanying fetal hyperinsulinaemia or fetal hyperglycaemia. Diabetes was induced by injecting streptozotocin (30-45 mg/kg, i.v.) on day 2 of gestation. Fetal adrenals were removed on day 20 of gestation and cultured. Streptozotocin caused moderate (blood glucose 14-22.5 mmol/l) to severe (blood glucose greater than 25 mmol/l) diabetes. Both moderate and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Glucocorticoid dynamics during diabetic pregnancy is a controversial issue. Plasma corticosterone levels at term are dependent on the severity of maternal diabetes [24]. Maternal and fetal plasma corticosterone levels of diabetic rats were significantly lower than the corresponding control values between GD19 and GD22 [25].…”
Section: Discussionmentioning
confidence: 85%
“…Glucocorticoid dynamics during diabetic pregnancy is a controversial issue. Plasma corticosterone levels at term are dependent on the severity of maternal diabetes [24]. Maternal and fetal plasma corticosterone levels of diabetic rats were significantly lower than the corresponding control values between GD19 and GD22 [25].…”
Section: Discussionmentioning
confidence: 85%
“…Conliffe and Mulay [12] observed that fetal rat plasma corticosterone appeared to be related to the degree of hyperglycemia. Cugini et al [27] have reported elevated aldosterone levels in the newborns of human diabetics.…”
Section: Discussionmentioning
confidence: 98%
“…Mulay and Solomon [10] reported decreased corticosterone levels in late gestation fetuses of moderately diabetic, untreated dams, whereas Gewolb and Warshaw [11] observed no difference in unbound corticosterone. Conliffe and Mulay [12] have shown that plasma corticosterone levels were lower in fetuses of moderately (which they defined as a maternal glucose of 21.4 mM/l) diabetic untreated gestations compared with control. However, DNA synthesis and basal in vitro production of corticosterone by dispersed fetal adrenal cells from these diabetic dams were unchanged upon addition of insulin or glucose to the media, leading the authors to conclude that neither insulin nor glucose exerted a direct effect in vitro upon fetal adrenal cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations